Correction of the Retracted Alar Base - Losquadro, William D.; Bared, Anthony; Toriumi, Dean M. (Facial Plastic Surgery, 2012)
Alar base retraction is a common yet difficult problem faced by the rhinoplasty surgeon. It may be caused by weakened, overresected lateral crura, vestibular lining deficiencies, or congenital alar malpositioning. Methods of correction include soft tissue manipulation, auricular composite grafting, and cartilage grafting. We present the senior author's graded approach to alar retraction using auricular composite grafting, alar rim grafting, and lateral crural strut graft placement with caudal lateral crural repositioning.
Keywords: rhinoplasty; alar retraction; lateral crural strut graft; composite graft